Errata: Volume 10; Issue 4, 2022 - International Journal of Medical Students, Executive Committee of the (International Journal of Medical Students, 2023)
The following items published in the International Journal of Medical Students (IJMS) Volume 10, Issue 4 of 2022 were corrected on February 20, 2023: "A Cross-Sectional Study of p66Shc Gene Expression in Liquid Biopsy of Diabetic Patients. Is it Possible to Predict the Onset of Renal Disease?" was corrected for capitalization errors in the title.1 "Elective Courses in Global Surgery for Undergraduate Medical Students: A Narrative Review and a Proposal for European Universities" contained an error in the DOI on the footer of page 395. The correct DOI is: 10.5195/ijms.2022.1598.2 "Why the Furor about Polio?" was corrected for a spacing error in the title in the PDF version.3 In the article entitled "Research Experience of Medical Students Collaborating in an International Peer Research Mentorship Program", there were errors in the fourth and fifth authors’ names. The correct names are: Aysha Zulfiqar and Tejaswini Ashok.4 "‘First, Do No Harm’… A Call to Re-evaluate the Wellbeing of Healthcare Staff" was corrected for a spacing error in the title.5